Tinjauan Kebutuhan Rak Penyimpanan Rekam Medis di RSUD Bangka Selatan - Ferina Ferina; Muniroh Muniroh; Daniel Happy Putra; Lily Widjaja (Publikasi Indonesia, 2022)
Medical record is a collection of facts or evidence of the patient's condition, past and current medical history and treatment written by the health professional who provides services to the patient. Medical records require sufficient storage shelves and storage space is needed to maintain confidentiality, avoid damage and make it easier for officers to retrieve and return medical records in the long term. If the medical record storage is adequate and meets the standards to support maximum patient care, it is necessary to adjust the need for medical record storage racks at the South Bangka Hospital. The purpose of this study was to determine the need for medical record storage racks for the next 5 years at RSUD South Bangka. This type of research uses a descriptive method with a quantitative approach. Data collection techniques used are observation and interviews. The results of this study are the number of medical record storage racks in the South Bangka Hospital currently amounts to 17 shelves and the South Bangka Hospital currently has a medical record storage area of 25m². It is recommended that the South Bangka Hospital need to provide 49 storage shelves for the next 5 (five) years so that the shelf needs can be met and can accommodate all medical records and it is hoped that the hospital will add an area of medical record room with an additional area of 11.96m² to adjust the addition of medical record racks.